Ayam Didik Sdn. Bhd. / Adnan Zulkifli ... [et al.] - Zulkifli, Adnan; Wan Ngah, Wan Mohd Khairul; Ibrahim, Baharum; Razilah, Nasrul Ridhwan; Zamaluddin, Mohammad Zahid (Faculty of Electrical Engineering, 2006)
This business is based on agreement between five (5) members. The group is consisting of the General Manager, Administration Manager, Marketing Manager, Financial Manager and Operational Manager. The business capital is amounted to RM 606,804. Total contribution from each member is RM 106,804 and the rest is loan from Bank Pertanian Malaysia.